Occurrence of Powdery Mildew on some Wild Plants from Khandesh Region of Maharashtra State - and Vidya A. Patil2, V. P. Pawar1 (Recent Research in Science and Technology, 2011)
Occurrence of Powdery Mildew on some Wild Plants from Khandesh Region of Maharashtra State